2019
DOI: 10.1080/09593330.2019.1650834
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanism of efficient mainstream partial nitritation/anammox (PN/A) in hybrid bioreactors (IFAS)

Abstract: An explanation of possible mechanism of efficient PN/A in hybrid bioreactors was presented. The bottleneck process is nitritation. Surplus nitrite production by ammonium oxidizing bacteria (AOB) is required for assuring the activity of anammox bacteria and eliminating nitrite oxidizing bacteria (NOB). It will be possible if nitrogen removal rate by AOB (r N_AOB ) is higher than NOB (r N_NOB ). It was shown that in biofilm AnAOB bacteria should out-compete NOB, whereas nitrogen transformation rates by AOB are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Meanwhile, many laboratory studies demonstrated stable mainstream one-stage PN/A performance in MBBRs, granule-based reactors, ,, and hybrid systems (biofilm and floccular sludge; Table S1). It was found that anammox can successfully cope with low temperatures (10–20 °C). , NOB can be stably suppressed over a long period (>1 year), and the effluent total N concentration can reach below 10 mg N L –1 at limiting DO concentrations (<0.2 mg L –1 ) …”
Section: Mainstream Pn/amentioning
confidence: 99%
“…Meanwhile, many laboratory studies demonstrated stable mainstream one-stage PN/A performance in MBBRs, granule-based reactors, ,, and hybrid systems (biofilm and floccular sludge; Table S1). It was found that anammox can successfully cope with low temperatures (10–20 °C). , NOB can be stably suppressed over a long period (>1 year), and the effluent total N concentration can reach below 10 mg N L –1 at limiting DO concentrations (<0.2 mg L –1 ) …”
Section: Mainstream Pn/amentioning
confidence: 99%
“…As mentioned in the literature, nitrogen transformation rates by AOB need to exceed those of NOB (by controlling the operating conditions) to ensure stable PN to provide nitrite for AnAOB. 33 Moreover, it should be pointed out that relying on ammonium accumulation to maintain NOB repression in PN/A evidently worsens the quality of the effluent. 10 However, with the PN/A-PDN/A process, the residual ammonium in the aerobic phase as well as the nitrate could be further removed in the following anoxic phase with limited organics (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions of low DO and appropriate residual bulk ammonium have been reported to effectively suppress NOB. ,, In this study, the abundance and bioactivity of NOB were continuously suppressed and remained below those of AOB for up to 250 days (Figures S2 and S7). As mentioned in the literature, nitrogen transformation rates by AOB need to exceed those of NOB (by controlling the operating conditions) to ensure stable PN to provide nitrite for AnAOB …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several operational control strategies have been employed in a two-stage configured system involving either suspended growth or attached growth systems to achieve stable partial nitritation. Recently, research has focused on hybrid system where attached growth biofilms and flocs coexist, also known as integrated fixedfilm activated sludge (IFAS) systems, and biofilm technologies such as the moving bed biofilm reactor (MBBR) system (Laureni et al, 2016(Laureni et al, , 2019Gu et al, 2018;Kowalski et al, 2019a;Gustavsson et al, 2020;Trojanowicz et al, 2021). Recent interest in biofilm technologies is due to their ability to retain highly specialized microbial populations and also because biofilm structure results in substrate gradients that can promote suppression of the growth of the NOB population or suppression of the NOB activity (Brockmann and Morgenroth, 2008;Gilbert et al, 2014;Pérez et al, 2014;Lotti et al, 2015a;Piculell et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%